2017
DOI: 10.1111/ppl.12615
|View full text |Cite
|
Sign up to set email alerts
|

The C2 protein of tomato leaf curl Taiwan virus is a pathogenicity determinant that interferes with expression of host genes encoding chromomethylases

Abstract: Tomato (Solanum lycopersicum) is one of the most important crops worldwide and is severely affected by geminiviruses. Tomato leaf curl Taiwan virus (ToLCTWV), belonging to the geminiviruses, was isolated in Taiwan and causes tremendous crop loss. The geminivirus-encoded C2 proteins are crucial for a successful interaction between the virus and host plants. However, the exact functions of the viral C2 protein of ToLCTWV have not been investigated. We analyzed the molecular function(s) of the C2 protein by trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Although full functionality of C2-GFP or GFP-C2 during the viral infection has not been demonstrated, C-terminal GFP fusions have been used in functional studies with other geminiviral C2 proteins (e.g. [ 42 45 ]). Local infection assays with two TYLCV mutant viruses unable to express CP, TYLCV-CPmut1 and TYLCV-CPmut2, in which early stop codons are introduced and alternative transcriptional initiation sites have been removed (for details, see Materials and Methods ), demonstrate that the presence of CP is not only sufficient, but also required for the re-localization of C2-GFP into the nucleolus in infected cells ( Fig 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…Although full functionality of C2-GFP or GFP-C2 during the viral infection has not been demonstrated, C-terminal GFP fusions have been used in functional studies with other geminiviral C2 proteins (e.g. [ 42 45 ]). Local infection assays with two TYLCV mutant viruses unable to express CP, TYLCV-CPmut1 and TYLCV-CPmut2, in which early stop codons are introduced and alternative transcriptional initiation sites have been removed (for details, see Materials and Methods ), demonstrate that the presence of CP is not only sufficient, but also required for the re-localization of C2-GFP into the nucleolus in infected cells ( Fig 3D ).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the geminiviral genome forms minichromosomes and is subjected to epigenetic modifications, including cytosine DNA methylation and histone modifications ( Ceniceros-Ojeda et al, 2016 ; Deuschle et al, 2016 ; Jackel et al, 2016 ; Kushwaha et al, 2017 ; Raja et al, 2008 ; Wang et al, 2018 ). The findings that methylation of viral DNA negatively impacts viral replication ( Brough et al, 1992 ; Ermak et al, 1993 ), that different geminivirus-encoded proteins have evolved to suppress DNA methylation ( Buchmann et al, 2009 ; Ismayil et al, 2018 ; Raja et al, 2008 ; Rodríguez-Negrete et al, 2013 ; Tu et al, 2017 ; Wang et al, 2018 ; Yang et al, 2013 ; Yang et al, 2011 ; Zhang et al, 2011 ), and that methylation of the viral genome correlates with host resistance or recovery ( Butterbach et al, 2014 ; Ceniceros-Ojeda et al, 2016 ; Raja et al, 2008 ; Torchetti et al, 2016 ; Yadav and Chattopadhyay, 2011 ) strongly support the idea that the plant-mediated methylation of the viral DNA acts as an antiviral defence mechanism, underscoring DNA methylation as an active battlefield in the interaction between plants and geminiviruses.…”
Section: Introductionmentioning
confidence: 99%
“… Li et al (2018) found that S-acylation of C4 was essential for beet severe curly top virus symptom determination. The C2 protein of tomato leaf curl Taiwan virus was shown to be an important pathogenicity determinant, which interferes with host DNA methylation ( Tu et al, 2017 ). To counteract RNA silencing defenses in plant, many geminivirus V2 proteins have been shown to serve as RNA silencing suppressors ( Yang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%